The relationship between respiratory function, functional exercise capacity, and the ankle-brachial index in patients with peripheral arterial disease - Aydin, Gamze; Kanan, Nesih (Elsevier Science Inc, 2025)
Purpose: Peripheral arterial disease (PAD) is a common clinical manifestations of atherosclerosis. The aim of this study is to investigate the relation of respiratory function and functional exercise capacity with the ankle-brachial index (ABI) in patients with PAD. Method: The study adopted a cross-sectional design. The respiratory function was measured using a spirometer through respiratory function tests. The following values measured: Forced Expiratory Volume in 1 s (FEV1), Forced Vital Capacity (FVC), FEV1/FVC ratio, 25 % Flow of Forced Vital Capacity (FEF25), 75 % Flow of Forced Vital Capacity (FEF75), and the average flow between 25 % and 75 % of Forced Vital Capacity (FEF25-75). Functional exercise capacity was assessed using the 6-Minute Walk Test (6MWT) and ABI was measured. Results: The study included 95 patients with PAD (mean age: 52.0 +/- 8.3 years). The mean ABI value was 0.86 +/- 0.17. The participants walked an average of 374.59 +/- 82.16 m in the 6MWT. There were positive correlation between ABI and FEV1, FVC, PEF, 6 MWT (r(s):0.56, p < 0.001; r(s):0.39, p < 0.001; r(s):0.34, p:0.001; r(s):0.64, p < 0.001, respectively). The other respiratory function outcomes also demonstrated significant positive relations with ABI (p < 0.05). Conclusion: This study demonstrated that increases in ABI values were associated with improvements in respiratory function and functional exercise capacity in patients with PAD. Evaluation of respiratory parameters in patients with PAD and the implementation of rehabilitation approaches aimed at improving respiratory function may positively contribute to the management of the disease. (c) 2025 Society for Vascular Nursing, Inc. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Ankle brachial index; functional capacity; peripheral arterial disease; respiratory function test